International Labor Migration and Remittances in Nepal (Journal of Population and Development, 2020)
International migration and remittance are major areas of population and development. This study identifies the trend and destination of foreign labor migration in Nepal and highlights the flow of remittance status and its contribution to the gross domestic product in Nepal. This study is based on the secondary data collected from the various national and international organizations. Migration from Nepal has expanded tremendously since the mid-1990s, accompanied by a continuous broadening of the variety of destinations. Nepal has observed a rapid increase of absent population over census periods. International migration for work has changed significantly as is evident in the growing outflow of temporary migration of youths, both men and women, to work in newly emerging economies like Malaysia, Qatar, Saudi Arabia, and United Arab Emirates. Emigration has come to be recognized as an important factor both for changing ways of life of people and for the positive contribution to the nation’s economy. In terms of remittance inflows as percent of GDP, Nepal is the third largest remittance receiver in the world. Taking all these factors into consideration, the only problem with it is that; until now, the government only seems to have adopted policies to encourage youth to find employment opportunities and provide remittance in turn but not for them to invest in productive sector to create more jobs and to retain working age population within the country.